2011
DOI: 10.1111/j.1748-5827.2011.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic findings in canine pyothorax and correlation with findings at exploratory thoracotomy

Abstract: CT and surgical findings are similar in most cases of canine spontaneous pyothorax. CT may be a useful diagnostic tool for guiding case management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Computed tomographic and surgical findings for spontaneous pyothorax in dogs have been previously evaluated and found to correlate in most cases. 24 This correlation is separate from the ability of CT to identify intraluminal MPA foreign bodies; prior reports have suggested weakness of CT in localizing MPA or foreign material in dogs and cats. 13,14,16,25 This weakness is apparent in the current study in which MPA that were highly suspected according to CT were identified in only a minority of animals and imperfectly correlated with surgical or bronchoscopic findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomographic and surgical findings for spontaneous pyothorax in dogs have been previously evaluated and found to correlate in most cases. 24 This correlation is separate from the ability of CT to identify intraluminal MPA foreign bodies; prior reports have suggested weakness of CT in localizing MPA or foreign material in dogs and cats. 13,14,16,25 This weakness is apparent in the current study in which MPA that were highly suspected according to CT were identified in only a minority of animals and imperfectly correlated with surgical or bronchoscopic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have identified filamentous bacteria, particularly Actinomyces spp, as important isolates in pyothorax cases thought to be associated with MPA. [2][3][4][11][12][13]24 Actinomyces spp are known inhabitants of normal canine oral flora and their role in pyothorax is presumably a result of inhaled foreign material seeding infection in previously normal tissue. 12 The relatively low rate of identification of these organisms within this cohort may be a result of the fastidious nature of Actinomyces spp as well as the high rate of preoperative antimicrobial therapy administered in the reported cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented severe mass‐like mediastinal pleural thickening secondary to pyogranulomatous mediastinitis in dogs with pyothorax and this could potentially lead to skewed results when comparing malignant pleural disease to all other effusion types combined; therefore, pleural changes in dogs with malignant pleural disease and pyothorax were combined together and compared to the other effusion types. The only predictive features found were any costal pleural abnormality and the presence of a pulmonary mass, for which there was a moderately high area under the receiver operating curve (0.75) and sensitivity (98%) but low specificity (45%).…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer studies in veterinary medicine assessing pleural abnormalities on CT in dogs and cats with pleural effusion with some studies simply describing nonspecific thickening of the parietal and/or visceral pleura . Several studies assess pleural abnormalities in more detail, including the assessment of Hounsfield units in different types of pleural effusion and assessing various types of pleural thickening (eg, smooth, irregular, nodular, mass), such as those seen with mesothelioma, carcinomatosis or other malignancies or with infectious pleuritis/mediastinitis associated with pyothorax such as secondary to foreign body migration or bronchopneumonia . One study assessed whether pleural abnormalities on CT in dogs can distinguish malignant from inflammatory (pyothorax and chylothorax) effusions and found that there were many overlapping pleural features, although the presence of any pleural thickening, marked pleural thickening involving only the parietal pleura and thoracic wall invasion, supported a diagnosis of malignancy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation